An investigation of stress experienced by caregivers of children with intellectual disability in a Western Cape Province population - Strachan, Sarah-Jessica (Department of Psychiatry and Mental Health, 2020)
Background: Intellectual disability (ID) is described as a neurodevelopmental disorder which occurs during the developmental period and impacts intellectual as well as adaptive functioning across social, cognitive and practical domains. Approximately 3 percent of the South African population has mild to severe forms of ID. It is well described that caregivers of children with ID and other developmental disorders have higher levels of stress related to caring for their child than parents with typically developing children. However, little research has been reported in the South African context. Objectives: 1. To determine the nature and extent of self-reported symptoms of stress in caregivers of children with intellectual disabilities. 2. To establish which demographic variables and child factors are associated with carer stress. 3. To compare the nature and extent of self-reported stress and demographic and child variables associated with stress in carers of children with intellectual disability with the same measures reported by carers whose children are developing typically. Methods: This was a purposive, descriptive analytical study. Participants were 59 caregivers whose children attended Red Cross War Memorial Children’s Hospital outpatient clinics. The ID group comprised 35 caregivers of children with ID. The control Non-ID group had 24 caregivers of typically developing children. The children’s ages ranged from 2 to 10 years. Caregivers were administered a set of four questionnaires: a demographic questionnaire; the Parent Stress Index; the Hospital Anxiety and Depression Scale and the Aberrant Behaviour Checklist that rated the children’s behaviour. The data were analysed using IBM SPSS. Results: Both the ID and Non-ID groups showed elevated scores for self-reported anxiety. The ID group of caregivers reported significantly more problem behaviours in their children than the caregivers in the Non-ID group. Hyperactive behaviour predicted for depression in the caregiver ID group which also reported higher levels of stress and significantly higher levels of depression than the Non-ID group. 49 percent of the ID group caregivers reported levels of depression in the clinical range. Further, the ID group reported significantly more financial difficulties and also more appointments for their child at health facilities than the control group. Conclusion: Carers in this study setting experienced similar stresses and described similar child behavioural problems as those reported internationally. A significant finding was the high rate of caregivers of children with ID whose depression scores were in the clinical range. Child behaviour was a significant factor associated with caregiver stress and anxiety in both study groups and with depression in caregivers of children with ID. The study findings have implications for the mental health and behavioural support needs of both caregivers of typically developing children and caregivers of children with ID and for a range of services that provide this support.